PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TERMINAL PENUMPANG PELABUHAN TANJUNG MAS SEMARANG - Yoeli Janto; Harcici Harcici (UNIMAR AMNI Semarang, 2019)
The purpose of this research is to analyze the influence between physical evidence, reliability, responsiveness, assurance, and empathy on customer’s satisfaction as in individuals and/or groups of customers of passenger terminal services at Tanjung Mas Port of Semarang. The population sampling used was 98 respondents. Data analysis was performed using multiple linear regression tests. Based on the results of the data analysis, it was concluded that the physical evidence, reliability, responsiveness, assurance on customer’s satisfaction as in individuals and/or groups of customers of passenger terminal services at Tanjung Mas Port of Semarang are influenced the passengers’ satisfaction on the service of Tanjung Mas Port passenger terminal. The magnitude of the influence of the five dimensions of services quality on consumer satisfaction is 64.3 percent. The regression equation formed is : Y =3,249 + 0.188 X1 + 0.150 X2 + 0.340 X3 + 0.270 X4 + 0.198 X5.Keywords: Service Quality, Consumer Satisfaction Penelitian ini bertujuan untuk menganalisis pengaruh dimensi tangible (bukti fisik), reliability (kehandalan), responsive (daya tanggap), assurance (jaminan) dan emphaty (empati) secara individu maupun bersama - sama terhadap kepuasan konsumen pengguna jasa terminal penumpang Pelabuhan Tanjung Mas Semarang. Sampel yang digunakan sebanyak 98 responden. Analisis data dilakukan dengan menggunakan uji regresi linier berganda. Berdasarkan hasil analisis data disimpulkan bahwa dimensi tangible (bukti fisik), reliability (kehandalan), responsive (daya tanggap), assurance (jaminan) dan emphaty (empati) secara individu maupun bersama - sama berpengaruh terhadap kepuasan konsumen pengguna jasa terminal penumpang Pelabuhan Tanjung Mas Semarang. Besarnya pengaruh kelima dimensi kualitas pelayanan terhadap kepuasan konsumen sebesar 64,3 persen. Persamaan regresi yang terbentuk adalah Y = 3,249 + 0,188 X1 + 0,150 X2 + 0,340 X3 + 0,270 X4 + 0,198 X5.Kata kunci : Kualitas Pelayanan, Kepuasan Konsumen